Efficient One‐Step Production of Microencapsulated Hepatocyte Spheroids with Enhanced Functions. Issue 20 (1st April 2016) - Chan, Hon Fai; Zhang, Ying; Leong, Kam W.
Abstract : Hepatocyte spheroids microencapsulated in hydrogels can contribute to liver research in various capacities. The conventional approach of microencapsulating spheroids produces a variable number of spheroids per microgel and requires an extra step of spheroid loading into the gel. Here, a microfluidics technology bypassing the step of spheroid loading and controlling the spheroid characteristics is reported. Double‐emulsion droplets are used to generate microencapsulated homotypic or heterotypic hepatocyte spheroids (all as single spheroids <200 μm in diameter) with enhanced functions in 4 h. The composition of the microgel is tunable as demonstrated by improved hepatocyte functions during 24 d culture (albumin secretion, urea secretion, and cytochrome P450 activity) when alginate‐collagen composite hydrogel is used instead of alginate. Hepatocyte spheroids in alginate‐collagen also perform better than hepatocytes cultured in collagen‐sandwich configuration. Moreover, hepatocyte functions are significantly enhanced when hepatocytes and endothelial progenitor cells (used as a novel supporting cell source) are co‐cultured to form composite spheroids at an optimal ratio of 5:1, which could be further boosted when encapsulated in alginate‐collagen. This microencapsulated‐spheroid formation technology with high yield, versatility, and uniformity is envisioned to be an enabling technology for liver tissue engineering as well as biomanufacturing. Abstract : Microencapsulated homotypic or heterotypic hepatocyte spheroids are generated by rapid cell assembly followed by hydrogel polymerization in the double‐emulsion droplet. The tunable hydrogel composition, combined with the use of endothelial progenitor cells as a novel supporting cell type, enhances the long‐term performance of hepatocytes. This high‐throughput microencapsulation technology with high yield and uniformity can be applied in various medical applications.